Data selection mapping in mobile decision making using MCDSS technique - Anom, Raja Baharuddin; Wahid, Mohd. Taib; Maarof, Mohd. Aizani; Ruskam, Aminuddun (Faculty of Computer Science and Information System, 2007)

(untitled)
Multi criteria decision support system (MCDSS) is a decion making technique used in a aplication and system development to help user to solve a problem and make a decision.Along with current computer technology evolution, request for mobile decision support system is increasing tremendously from time to time. These scenario leads to a new requirement for data mapping and decision suport technique in order to support many newborn decision support sistem nowadays. This project focusing on decision support system technique and data mapping technique development from a central server into a mobile device to fullfil decision support system requirement in mobile enviroment using multicriteria decision support technique..